Efficacy and safety of combination of frankincense and botulinum toxin in the treatment of blepharospasm: a protocol for a single-centre, open-label, randomized, controlled trial - Gong, Shiyuan; Luo, Yuhan; Zhang, Jiana; Huang, Feiwen; Yang, Zhengkun; Zhang, Yue; Ou, Zilin; Yan, Zhicong; Zhang, Weixi; Zhou, Qian; Liu, Gang (Frontiers in Neurology, 2025)
IntroductionBlepharospasm (BSP) is a functionally disabling disease with a marked impact on the quality of life of patients. Botulinum toxin (BoNT) injections have been recommended as first-line therapy for BSP. However, the clinical benefits of BoNT are temporary with only about 8–10 weeks duration of benefit in most patients with BSP. Per previous case reports, regular use of topical frankincense essential oil (FEO) can achieve significant symptom relief and can decrease the frequency of BoNT injections. This trial will explore whether BoNT combined with regular application of FEO can improve clinical outcomes in patients with BSP.Methods and analysisThis protocol describes an open-label, randomized controlled trial to be undertaken to evaluate daily topical application of FEO and coconut oil (CO) in patients with BSP. The goal is to enroll 32 patients with BSP who have received immediate BoNT injection in each treatment arm. Only patients who have previously received less than 12 weeks of positive benefits from BoNT therapy will be enrolled. The primary outcome will be the duration of symptom improvement after the intervention with BoNT combined with FEO or CO within the 24-week follow-up period. Symptom improvement is defined as a decrease of one point or more in the Jankovic Rating Scale severity score compared to baseline in patients with BSP. Secondary outcomes will consist of changes in BSP symptom severity, disability, and quality of life from baseline to each time point after the intervention. Safety analysis will be based on the presence of localized skin allergic reactions and adverse events. Outcomes will be assessed at baseline and at weeks 2, 4, 8, 12, 16, 20, and 24 after the therapy begins.DiscussionThis study will provide evidence that FEO therapy is a promising non-invasive therapy that can be easily combined with BoNT injections to improve clinical outcomes in patients with BSP.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400091987.